2010
DOI: 10.1002/mnfr.200900320
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects on granulosa cells of hydroxylated and methylated resveratrol analogues

Abstract: Several resveratrol analogues have been designed to improve bioactivity: among these polymethoxystilbenes appear to be particularly promising. The present study was set up to investigate the biological functions of polymethoxystilbenes 2 and 3, recently found in our lab as antiangiogenic agents, on a well-defined swine granulosa cell model. Proliferative activity and effects on steroidogenesis were evaluated, as well as the effect on granulosa cell vascular endothelial growth factor (VEGF) production, since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
1
39
2
Order By: Relevance
“…Although the underlying mechanisms of resveratrol-induced inhibition of aromatase is still poorly understood, it has been suggested that both binding to estrogen receptors and/or a modulation of cell signaling pathways may be involved (50). This resveratrol-induced inhibitory effect on aromatization is in sharp contrast with a previous study, whereby stimulation of steroidogenesis by a hydroxylated resveratrol analog was shown in a swine granulosa cell model (51). These marked discrepancies on granulosa cell steroidogenesis between the parent compound and the hydroxylated resveratrol analog may be due to the fact that the hydroxyl group could act at a proximal point of the steroid biosynthetic pathway, thus stimulating both progesterone and estradiol production.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the underlying mechanisms of resveratrol-induced inhibition of aromatase is still poorly understood, it has been suggested that both binding to estrogen receptors and/or a modulation of cell signaling pathways may be involved (50). This resveratrol-induced inhibitory effect on aromatization is in sharp contrast with a previous study, whereby stimulation of steroidogenesis by a hydroxylated resveratrol analog was shown in a swine granulosa cell model (51). These marked discrepancies on granulosa cell steroidogenesis between the parent compound and the hydroxylated resveratrol analog may be due to the fact that the hydroxyl group could act at a proximal point of the steroid biosynthetic pathway, thus stimulating both progesterone and estradiol production.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, a resveratrol-induced decrease in VEGF expression has been demonstrated in several human cancer cell lines (5658). Additionally, Basini et al demonstrated that the treatment of swine granulosa cells with two resveratrol analogs, hydroxylated and methylated forms, also decreased VEGF output (51). These observations may be relevant to the treatment of several gynecological disorders, as abnormalities in ovarian angiogenesis contribute to OHSS seen in women with PCOS, to disorders of ovulation, to subfertility and to endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…21 Several RSV analogues have been synthesized to improve the biological activity of the molecule. 15,22,23 In our previous studies, different trans RSV derivatives revealed a structure-activity relationship. In particular, we have demonstrated that the hydroxyl group in the 4 0 position is required for the antioxidant activity; in contrast, the presence of 4 0 -OH together with stereoisometry in the trans conformation (4 0 -hydroxystyryl moiety) was required for the inhibition of cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…It is a phytoestrogen known to bind equally to estrogen receptors α and β [24], and structurally similar to synthetic estrogens, such as DES and 17β-estradiol benzoate [25]. In contrast to its hyperproliferative effects, resveratrol promoted apoptosis in rat ovarian theca-interstitial cells [12], and its analogues inhibited swine GC growth [13]. It was also reported that resveratrol inhibited the proliferation of a wide variety of human cancer cell lines through the induction of S-phase cell cycle arrest and apoptosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that SIRT1 activator resveratrol plays a role in reproductive biology. Resveratrol was shown to modulate theca cell proliferation [12], and methylated resveratrol analogues possessed biological activities in swine GCs [13]. In the present study, to assess a role of SIRT1 in the regulation of reproductive axis in female, we investigated the expression of endogenous SIRT1 in human and rat GCs and the effect of resveratrol on cellular viability and steroidogenesis in rat GCs.…”
Section: Introductionmentioning
confidence: 99%